Fibrocartilaginous dysplasia (fibrous dysplasia and massive cartilaginous differentiation): Case report and literature review: Fibrocartilaginous dysplasia - Yılmaz, Fatih; Canaz, Funda; Yılmaz, Evrim; İnan, Ulukan (Journal of Surgery and Medicine, 2022)
Fibrocartilaginous dysplasia (fibrous dysplasia and massive cartilaginous differentiation or fibrochondroplasia, FCD) is a rare variant of fibrous dysplasia and a term used for cases of fibrous dysplasia with prominent cartilage tissue. A limited number of FCD cases have been reported in the literature, which can be seen in both clinical forms. A 16-year-old male patient, who had been followed for ten years with a diagnosis of polyostotic fibrous dysplasia in the left hip and cranium, presented with pain in the left leg after a fall. A subtrochanteric pathological fracture in the left femur was detected on exam, the lesion area was curetted, and osteotomy and fixation were applied. Microscopic assessment revealed a fibro-osseous lesion of benign spindle cell fibrous connective tissue with woven bone trabeculae, without osteoblastic rim or large areas of benign cartilage nodules. The final diagnosis was fibrocartilaginous dysplasia. In our literature review, 26 cases of FCD were reported so far. Age distribution of patients ranged from 4 to 53 years (mean 15.9) and the male / female ratio was 15/11 = 1.36. Eighteen cases were monostotic, and 8 were polyostotic. In cases with noted clinical and follow-up data, symptom duration ranged from 8 weeks to 18 years (mean 62.2 months), with no recurrence or malignant transformation in a mean follow-up of 21.71 (2-60) months post-treatment. In the cartilage component, there was increased cellularity, some nuclear atypia, binucleation, and myxoid degeneration. This situation simulates benign and malignant entities such as enchondroma, fibrocartilaginous mesenchymoma, well-differentiated intramedullary osteosarcoma, and chondrosarcoma with a differential diagnosis. FCD is a benign and very rare lesion with a prominent chondroid component, but may cause difficulty with differential diagnosis. Awareness of the histopathological and radiological features of FCD cases, their age range, and involvement areas provides an approach to distinguish them from lesions that may be confusing in a differential diagnosis.